2017
DOI: 10.1002/ird.2108
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Design of Drip Irrigation System using Water and Fertilizer Application Uniformity at Different Operating Pressures in a Semi‐Arid Region of India

Abstract: Performance evaluation of irrigation has been an important area of research for better management of water resources. The present study was conducted to evaluate the effect of drip lateral lengths and system operating pressures on water and fertilizer application uniformity at the Indian Agricultural Research Institute (IARI), New Delhi, India. The following parameters of nutrients and water were studied to design and evaluate the performance of drip irrigation systems: (i) uniformity coefficient; (ii) dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(14 reference statements)
1
6
0
1
Order By: Relevance
“…e water quality values showed that the groundwater (IT 2 ) was saline (EC iw 1.5 to 3.0 dS.m −1 , pH < 8.0, and SAR < 10.0). e uniformity of the drip irrigation system was satisfactory and in line with the past study [34] which reported the highest uniformity coefficient (99.2%). e distribution uniformity (97.4%) was found under the drip irrigation at a pressure of 1.5 kg cm −2 using a 25 m long lateral line in New Delhi, India.…”
Section: Crop Yield and Water Use Efficiencysupporting
confidence: 87%
“…e water quality values showed that the groundwater (IT 2 ) was saline (EC iw 1.5 to 3.0 dS.m −1 , pH < 8.0, and SAR < 10.0). e uniformity of the drip irrigation system was satisfactory and in line with the past study [34] which reported the highest uniformity coefficient (99.2%). e distribution uniformity (97.4%) was found under the drip irrigation at a pressure of 1.5 kg cm −2 using a 25 m long lateral line in New Delhi, India.…”
Section: Crop Yield and Water Use Efficiencysupporting
confidence: 87%
“…The socioeconomic impacts of rainfall are significant, from physical damage in floods to disruptions in transport networks [3,9]. Simultaneously, India is challenged with increasing population and climate change, which have threatened the present freshwater need for irrigation and drinking [10][11][12][13]. To overcome the challenges of water scarcity and the deterioration of cultivable land, modeling rainfall-runoff plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Irrischeduler was developed to indicate the time for irrigation based on the soil moisture level. 12 If tea lacks nutrients, it will influence the yield and quality of the tea, and even the production. When tea leaves lack nutrients, it is difficult for experts to confirm the diagnosis if the symptoms are not clear or complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Irrischeduler was developed to indicate the time for irrigation based on the soil moisture level. 12…”
Section: Introductionmentioning
confidence: 99%